SÍNTESE VERDE DE CARBOXILATOS METÁLICOS DERIVADOS DE RESINA DE PINUS APLICADOS COMO PIGMENTOS ANTIBACTERIANOS E ANTIVIRAIS - CORREA, JAMILLE DE SOUZA (2022)
Green synthesis of Metal-abietate complexes obtained from Pinus elliottii resin with antibacterial and antiviral properties is reported. The synthesis method used pine resin from reforestation, and an aqueous solution of metal sulfates (Mn, Fe, Co, Ni, Cu, and Zn) at a mild temperature (90 ◦C), without the use of organic solvents. Infrared vibrational spectra identify monodentate coordination mode for the Mn-abietate, Fe-abietate, Co-abietate and Cu-abietate complexes, and bidentate coordination mode for Ni-abietate and Zn-abietate. Mass spectrometry analysis shows molecules oxidations and the number of abietate ligands of each complex according to the metal. The morphological study by scanning electron microscopy indicates the tendency to shape pseudospheres; however, the Cu-abietate sample presents a lamellar morphology. The complexes show chemical stability and compatibility with application as inorganic pigments. The XPS results confirm the characteristic components of carboxylate ligands and the metal oxidation states (Mn3+, Fe3+, Co2+, Ni2+, Cu2+, and Zn2+); however, some samples show states mixtures. The complexes present different colors, and the metallic ion is the main responsible for the CIE parameters L*a*b*. In addition, the colorimetric coordinates change after the dispersion in paint. Complexes showed good activity against Staphylococcus aureus in the preliminary test. The antibacterial efficiency was evaluated using the JIS Z 2801: 2010 standard. Samples containing 10% and 20% (m/m) of Zn-abietate in commercial paint lead to the highest inhibition (>99.99%) against Staphylococcus aureus and Escherichia coli. Antiviral tests were performed according to the adapted ISO 22196:2011 standard using 10% (m/m) pigments in commercial paint. The samples with the best viricidal potential were Co-abietate and Cu-abietate, with an inhibition rate greater than 99.99% against Coronavirus (SARS-CoV-2). Because of its high antibacterial and antiviral efficiencies, the pigments have great potential to be explored in the paint industry for home and hospital environments.